2015
DOI: 10.3389/fnbeh.2015.00104
|View full text |Cite
|
Sign up to set email alerts
|

Linking appraisal to behavioral flexibility in animals: implications for stress research

Abstract: In fluctuating environments, organisms require mechanisms enabling the rapid expression of context-dependent behaviors. Here, we approach behavioral flexibility from a perspective rooted in appraisal theory, aiming to provide a better understanding on how animals adjust their internal state to environmental context. Appraisal has been defined as a multi-component and interactive process between the individual and the environment, in which the individual must evaluate the significance of a stimulus to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…The hippocampus has previously been implicated in fear generalization, a role variously described as supporting pattern separation of perceptually similar cues to minimize stimulus-based fear generalization [55] or as biasing behavior during uncertain expectation by strengthening the representation of aversive potential outcomes [13,56]. The current findings support a hippocampal role in ambiguity-based fear generalization and suggest an important role for ongoing neurogenesis, in particular, possibly in predicting or weighting possible outcomes associated with different behavioral options [57,58] and/or in emotional biasing of decisions [13,16,56,59]. …”
Section: Discussionsupporting
confidence: 59%
“…The hippocampus has previously been implicated in fear generalization, a role variously described as supporting pattern separation of perceptually similar cues to minimize stimulus-based fear generalization [55] or as biasing behavior during uncertain expectation by strengthening the representation of aversive potential outcomes [13,56]. The current findings support a hippocampal role in ambiguity-based fear generalization and suggest an important role for ongoing neurogenesis, in particular, possibly in predicting or weighting possible outcomes associated with different behavioral options [57,58] and/or in emotional biasing of decisions [13,16,56,59]. …”
Section: Discussionsupporting
confidence: 59%
“…Such knowledge, become essential to understand individual variability and the adjustment of organisms to changing environments (Faustino et al . ). Moreover, research into affective states or cognition skills of animals have made significant progress over the recent years (Paul et al .…”
Section: Current Issues In Farmed Fish Welfarementioning
confidence: 97%
“…In particular, it has been suggested that cognitive biases arising from the interference of affective states, as well as genetic and environmental factors, can affect the appraisal of ambiguous situations, which subsequently shapes resilience to stressful events [86]. One example is Harding and colleagues’ classic finding that rats exposed to unstable housing conditions made more pessimistic evaluations of ambiguous stimuli, in a way that is similar to how anxious or depressed people tend to make negative judgments about ambiguous stimuli [87].…”
Section: The Role Of Systemsmentioning
confidence: 99%